2015
DOI: 10.1007/s11547-015-0559-4
|View full text |Cite
|
Sign up to set email alerts
|

Postmortem-computed tomography and postmortem-computed tomography–angiography: a focused update

Abstract: The use of multidetector CT (MDCT) represents a reality routinely used in several forensic institutes, for the numerous advantages that this diagnostic tool can provide; costs are becoming increasingly lower; data acquisition is always faster and once acquired may be revalued at any time. However, there are also some diagnostic limitations, for example, the visualization of the vascular system or a limited soft tissue contrast. In order to overcome these limitations, in recent years, contrast medium has been i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(9 citation statements)
references
References 90 publications
(112 reference statements)
0
7
0
2
Order By: Relevance
“…A search for alternative post-mortem diagnostics has followed the decline in clinical autopsy rates [ 1 ]. The literature dedicated to post-mortem imaging and its developments is expanding, especially in the field of forensic medicine [ 2 , 3 , 4 , 5 , 6 ]. However, post-mortem imaging remains underutilized in daily clinical practice, and as a consequence, the literature on the clinical application of post-mortem imaging is limited.…”
Section: Introductionmentioning
confidence: 99%
“…A search for alternative post-mortem diagnostics has followed the decline in clinical autopsy rates [ 1 ]. The literature dedicated to post-mortem imaging and its developments is expanding, especially in the field of forensic medicine [ 2 , 3 , 4 , 5 , 6 ]. However, post-mortem imaging remains underutilized in daily clinical practice, and as a consequence, the literature on the clinical application of post-mortem imaging is limited.…”
Section: Introductionmentioning
confidence: 99%
“…Postmortem CT was introduced in 1977 for forensic use [6,19], with the first reported use for autopsy in 1983 for identifying gas in the brain of a Navy diver [19,31]. Postmortem CT was first suggested as a possible alternative to autopsy in 1994, although the authors described that the combination of CT and autopsy provided the most information [32].…”
Section: Introductionmentioning
confidence: 99%
“…Multidetector CT technique has replaced single-detector technique for postmortem imaging and appears to be most helpful for assessing skeletal pathology [2,12,20,33], and it might also be helpful in identifying intracranial hemorrhage [34,35]. Numerous authors have reported applications of postmortem CT angiography to investigate vascular pathology and determine sites of large vessel hemorrhage [31,36,37], and CT angiography has been used to evaluate congenital heart disease [19]. Ventilated postmortem CT is another variation of CT technique in adults that allows for better differentiation between postmortem lung changes and underlying antemortem lung pathology [38].…”
Section: Introductionmentioning
confidence: 99%
“…In the past 15 years, post-mortem computed tomography (PMCT) has emerged as an important imaging procedure in forensic pathology, especially to be able to provide necropsy detection of lesions and also determination of the cause of death [2,3]. Currently, transitional necropsy is considered as a gold standard and PMCT as an adjuvant method for investigation of the cause of death in both humans and animal.…”
Section: Introductionmentioning
confidence: 99%